Efforts to Improve Employee Performance through Employee Voice and Reward and Recognition - Vidya Dwi Amalia Zati; Syaifuddin Syaifuddin; Safiyan Safiyan (Proceeding of The International Conference on Economics and Business, 2023)
This study aims to directly determine the effect of employee voice, reward, and recognition on employee performance. This type of research is causal, where research data is obtained through distribution to 115 employees in 10 public junior high schools in Medan City. Data analysis using Structural Equation Modeling (SEM) based on Smart PLS. The results prove that direct employee voice, reward, and recognition significantly affect employee performance. The implications of the findings in this study indicate that employees in public junior high schools in Medan City expect employee appraisal rewards every year for outstanding employees. In addition, a form of recognition in leadership recognition or appreciation for each employee contributes to the activities that have been worked optimally.